As contribuições de uma oficina com o uso de materiais didáticos para formação inicial de licenciados do curso de licenciatura integrada da UFPA - SOARES, João Paulo Vasconcelos (2020)
In this work we seek to understand the contributions of a workshop with the use of didactic materials such as the abacus and the decimal pipe - which show different ways of teaching mathematics -, that was offered with the intention of collaborating in the training of undergraduates by giving meaning to some mathematical rules, in particular, why the numbering system is decimal and positional and why it "goes one" and "lends one", in solving the algorithms of fundamental operations, which are often explained superficially, indicating mere memorization. In order to do so, we focus on authors such as Lorenzato (2009), Turrioni and Perez (2009), Nacarato (2005), Botas and Moreira (2013), Silveira e Silva (2013) who discuss teacher training, pointing to the need for initial and continuous training, such as those given through activities carried out in mathematics labs and research projects that teach pedagogical strategies that aim to help teachers to attribute meanings to mathematical contents, that sometimes are not clear in expository classes. Thus, we performed a workshop with the use of the abacus and decimal pipe that was developed with graduates of the Integrated Degree in Science, Mathematics and Languages of the Federal University of Pará. This workshop consisted of a presentation of the objects, where and how this material can be used in the teaching of Mathematics, a proposal of construction and suggestions of activities. After its realization, participants were asked to answer a questionnaire, describing their reflections and learning through the use of manipulable objects. In our analyzes we noticed that the workshop contributes to the training of the undergraduates, considering that it showed the relevance of the use and reflection on the didactic materials that serve as support for the teacher in the accomplishment of his educational practice, allowing to understand the way in which they must be used in mathematics instruction to assist students in understanding the "whys" of this knowledge, as well as instigated them to use the learning obtained for their school activities, such as stages, and in the future in the labor camp.